(829) On The Planning Method "PERT" and its Application in the GDR حول طريقة التخطيط ”PERT“ وتطبيقها في جمهورية ألمانيا الديمقراطية - Habil Reinhard Goettner. (INP, 2024)
Stochastic models of network techniques are based on a network that illustrates the flow of the overall process and its partial processes. This network is prepared similarly to the critical path method. However, there are some differences in time planning. The PERT (Program Evaluation and Review Technique) method is based on a stochastic model. The various quantities used are not unambiguously determined as in the critical path method; instead, activity times, event dates (except for the project's start), and the overall duration time reflected in the network are interpreted stochastically. It is assumed that activity time cannot only be represented as a time value but as a probability distribution. This results in the impossibility of determining dates unambiguously; for example, one cannot say that the finish date of an activity will be on July 15th. Instead, it can only be stated that the finish date is expected with a certain percentage of probability within a time range.